Brain Waves Evaluation of Sound Therapy in Chronic Subjective Tinnitus Cases Using Wavelet Decomposition - Asadpour, Abdoreza; Jahed, Mehran; Mahmoudian, Saeid (Frontiers in Integrative Neuroscience, 2018)
Management and treatment of subjective tinnitus is an ongoing focus of research activities. One of the most viable assessments of such treatment is the evaluation of brain activity in addition to patient response and clinical assessment. This study focuses on sound therapy and evaluation of patients’ electroencephalogram (EEG) in order to verify its potency. Broadband sound therapy was applied to nineteen participants aging from 25 to 64 and suffering from chronic subjective tinnitus in order to investigate brain activity, a) before fake treatment, b) after fake treatment, and c) after the main treatment, using EEG and Visual Analog Scale (VAS) for evaluating Residual Inhibition (RI). Four features were extracted using 4-level wavelet decomposition with Symlet 8 as the mother wavelet. After the main treatment, the mean value of wavelet coefficients for each wavelet level was found to be lower in the region of interest (ROI) using T-Test with significance level of 0.01, in comparison to “before the treatment” for cases with decreased tinnitus loudness. These results indicate that tinnitus may cause additional brain activity in the delta band of the EEG and after an appropriate suppression through the broadband sound therapy, this activity decreases.